Understanding Accounting Students' Career Intention In Islamic Banking: Experience from Garut, Indonesia - Fitri Syakinah; Irfan Rizki Gumilar; Alam Avrianto (Fakultas Ekonomi Universitas Garut, 2023)
This study aims to investigate the factors influencing accounting students' intention to pursue a career in Islamic banking, by using a structural equation model. The study combines the Theory of Planned Behavior (TPB) and the religiosity concept to examine the effects of soft skills self-efficacy, technical skills self-efficacy, social influence, job market consideration, and Islamic religiosity on accounting students' intention to pursue a career in Islamic banking. Data were collected through a survey of 264 accounting students at Universitas Garut. The results show that soft skills self-efficacy, social influence, and Islamic religiosity have a significant positive impact on student's intention to pursue a career in Islamic banking. However, technical skills self-efficacy, and job market consideration do not significantly influence students' intentions. These findings provide insight for Islamic banks on how to attract potential employees to pursue a career in Islamic banking. The study contributes to the literature by incorporating Islamic religiosity in the TPB model to explain accounting students' career intentions in Islamic banking, which is particularly relevant in the context of Indonesia, a predominantly Muslim country.